Evaluation of methanol preservation for molecular and morphological studies in cyanobacteria using Planktothrix agardhii - Churro, Catarina (2016)
Molecular studies on cyanobacteria often involve filtering and freezing of samples leading to loss of cell morphological features. Methanol is often used in preservation of biological materials in association with other fixatives. This study evaluates the application of methanol in the preservation of DNA for molecular studies as well as for the preservation of cell morphology for morphometric analysis in filamentous cyanobacteria. In the present study, both culture and environmental bloom samples were preserved using a cold methanol dehydration series (50, 70, and 100 %) and stored at −20 °C for up to 2 years. The DNA quantity and quality, nucleotide sequence retrieval, and real-time PCR quantification were analyzed over time. Morphometric cell analysis was performed on preserved samples. Results show that the DNA extracted from samples preserved up to 6 months was successfully quantified by real-time PCR. After that period, the DNA quantity decreased with the preservation time. Nevertheless, we were able to detect/amplify the target fragment in samples preserved up to 2 years. The DNA sequence and cell morphology were also maintained during the preservation time. Thus, methanol preservation is an adequate method to preserve molecular information and morphological features after long storage periods.